2023
DOI: 10.3934/jimo.2021181
|View full text |Cite
|
Sign up to set email alerts
|

Pricing, carbon emission reduction and recycling decisions in a closed-loop supply chain under uncertain environment

Abstract: <p style='text-indent:20px;'>This paper studies the pricing and recycling decision problems in a closed-loop supply chain (CLSC) containing a manufacturer, a downstream retailer, and a third-party recycling left. The manufacturer is subjected to the cap-and-trade regulation and determines the wholesale price of products and carbon emission reduction rate. The retailer determines its resale price to meet customer demands. The third-party recycling left determines the collection rate of recycling and reman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This was endorsed by Mathieu (2001), Oliva and Kallenberg (2003) and Vandermerwe and Rada (1988), who stated that such a transition has helped manufacturing firms increase their profitability and ensure a reliable market share. Yan et al (2021) are of the opinion that eco-friendly and carbon credit-saving manufacturers, such as those who servitise, command better prices in the market, which argues well for servitization. Mattsson (1973) and Hannaford (1976) were some of the pioneers in writing about servitization when they put forward the system-selling concept.…”
Section: Structure Of Research Papermentioning
confidence: 99%
“…This was endorsed by Mathieu (2001), Oliva and Kallenberg (2003) and Vandermerwe and Rada (1988), who stated that such a transition has helped manufacturing firms increase their profitability and ensure a reliable market share. Yan et al (2021) are of the opinion that eco-friendly and carbon credit-saving manufacturers, such as those who servitise, command better prices in the market, which argues well for servitization. Mattsson (1973) and Hannaford (1976) were some of the pioneers in writing about servitization when they put forward the system-selling concept.…”
Section: Structure Of Research Papermentioning
confidence: 99%
“…e findings indicated that CLSC benefits are maximized under centralized decision making. Yan et al [34] examined the optimal collecting strategy in a CLSC consisting of a manufacturer, retailer, and third-party collector, considering carbon cap-and-trade policies. Xu et al [35] examined how CLSCs with hybrid and dedicated structures were affected by several carbon policies.…”
Section: Ce Reduction In Supplymentioning
confidence: 99%
“…Since recycling of old products has actually become the choice of more and more manufacturers on the basis of low-carbon initiatives, the model established in this paper is more in line with the actual production process of manufacturer enterprises, and the conclusions drawn are more realistic and instructive. The following are the main contributions made by this paper: Most available articles are limited to examining restrictions on either the recycling rate or carbon trading price by law [ 17 , 18 , 19 , 20 ], or the comparison among different recycling channels and models as well as the advantages and disadvantages of different carbon rights allocation policies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Different from most of the existing studies, this paper considers both the legal constraints on recycling rates and the carbon trading mechanism and studies their simultaneous effects on the decision making and profitability of members of the two-cycle closed-loop supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Most available articles are limited to examining restrictions on either the recycling rate or carbon trading price by law [ 17 , 18 , 19 , 20 ], or the comparison among different recycling channels and models as well as the advantages and disadvantages of different carbon rights allocation policies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Different from most of the existing studies, this paper considers both the legal constraints on recycling rates and the carbon trading mechanism and studies their simultaneous effects on the decision making and profitability of members of the two-cycle closed-loop supply chain.…”
Section: Introductionmentioning
confidence: 99%